2017
DOI: 10.1016/j.urology.2016.10.044
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of a Multimodal Treatment Paradigm to Accelerate Drug Evaluations in Early-stage Metastatic Prostate Cancer

Abstract: OBJECTIVE To evaluate a multimodal strategy aimed at treating all sites of disease that provides a rapid readout of success or failure in men presenting with non-castrate metastatic prostate cancers that are incurable with single modality therapy. MATERIALS AND METHODS Twenty selected men with oligometastatic M1a (extrapelvic nodal disease) or M1b (bone disease) at diagnosis were treated using a multimodal approach that included androgen deprivation, radical prostatectomy plus pelvic lymphadenectomy (retrope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 32 publications
0
53
0
11
Order By: Relevance
“…Extrapelvic lymph node metastasis is another important factor in decision-making; however, its presence is commonly underestimated with conventional staging methods. [ 32 33 34 35 ] In our study, we found that 17.31% of patients had retroperitoneal lymph node metastasis without evidence of hematogenous spread (M 1a ). In addition, PSMA PET-CT showed incremental value in the detection of inguinal and mediastinal lymph node metastasis, contrasting it from conventional methods.…”
Section: Discussionmentioning
confidence: 53%
“…Extrapelvic lymph node metastasis is another important factor in decision-making; however, its presence is commonly underestimated with conventional staging methods. [ 32 33 34 35 ] In our study, we found that 17.31% of patients had retroperitoneal lymph node metastasis without evidence of hematogenous spread (M 1a ). In addition, PSMA PET-CT showed incremental value in the detection of inguinal and mediastinal lymph node metastasis, contrasting it from conventional methods.…”
Section: Discussionmentioning
confidence: 53%
“…Recent results have encouraged exploration of a multimodal strategy in oligometastatic advanced prostate cancer, especially because studies suggest that each modality contributes to further disease debulking and, thus, disease control (87). Several studies are evaluating this strategy, including PEACE1 (NCT01957436), MetaCure (NCT03436654), and the radiotherapy arm of MRC STAMPEDE.…”
Section: Locoregional Therapy In Metastatic Prostate Cancermentioning
confidence: 99%
“…These results are in line with the data reported by the most recent literature. 13 , 14 We suggest that cytoreductive RP in combination with metastasis-directed SBRT is a feasible cytoreductive treatment strategy and has the potential to postpone disease progression to CRPC in PCa patients with synchronous bone oligometastases.…”
Section: Discussionmentioning
confidence: 99%